The role of morphological verification in determining the volume of surgery. A case of atypical hemangioma of the paranasal sinuses - P. V. Svetitsky; Yu. V. Ulyanova; O. V. Nistratova (Опухоли головы и шеи)
In this report we present a case of patient with a tumor of the paranasal sinuses. A non-homogeneous formation spreading to the right maxillary sinus, right nasal cavity, and right orbit (with the destruction of the bone wall of the anterior cranial fossa) in the ethmoid bone was detected on a computed tomography scan. A esthesioneuroblastoma was suspected after the needle biopsy (accompanied by bleeding). To clarify the diagnosis and to determine treatment strategy, we performed open biopsy under general anesthesia, which showed that the patient had hemangioma. The patient underwent radical removal of the tumor. Histopathological examination confirmed the diagnosis of hemangioma.The aim of this study was to describe a case of orbital tumor, when the results of needle biopsy were inconsistent with clinical manifestations.In this case, clinical manifestations had the decisive role in determining treatment strategy.